The IMPLEMENTATION OF ASSESSMENT IN TEACHING ENGLISH IN MERDEKA CURRICULUM - Dewa Ayu Made Juli Astari; Ni Nyoman Padmadewi; Ni Luh Putu Eka Sulistia Dewi (UIBU, 2023)
This study aimed to examine the implementation of assessment in teaching English within the Merdeka curriculum at SMK N 3 Sukawati. This study investigated the implementation of formative assessment in teaching English in the Merdeka curriculum. This research employed a case study. The subjects of this study were two tenth-grade English teachers selected using a purposive sampling technique and also tenth-grade students. The data were collected and analysed using qualitative methods. Observation, document analysis, and interviews were employed to gather the data. This study used the theory from Miles and Huberman (1994). The study revealed that teachers had quite optimally implemented formative. Teachers used performance through presentations and role-play for formative assessment. In addition, lacks were also found when the teachers carried out the assessment, namely, the teacher did not use the assessment rubric and did not provide feedback on student assessment results